2005
DOI: 10.1111/j.0737-1209.2005.220202.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Physical Activity and Low‐Fat Diet Among Low Income African American and Hispanic Middle School Students

Abstract: African Americans, Hispanics, and those with low income experience disproportionate health problems that can be prevented by physical activity and a lower fat diet. In this descriptive cross-sectional study, antecedents of diet and exercise within the Health Promotion/Transtheoretical Model were examined among low-income African American and Hispanic seventh-grade students (n = 127). Total support was associated with higher physical activity for girls. African Americans perceived greater social support for act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 34 publications
2
35
1
Order By: Relevance
“…However, the pattern of differences-with boys reporting more "favorable" cognitions in all four variables where differences were found-is consistent with previous research. For instance, Frenn et al (2005) found that Hispanic boys reported more vigorous physical activity than did girls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the pattern of differences-with boys reporting more "favorable" cognitions in all four variables where differences were found-is consistent with previous research. For instance, Frenn et al (2005) found that Hispanic boys reported more vigorous physical activity than did girls.…”
Section: Discussionmentioning
confidence: 99%
“…Hispanic seventh-grade children reported less total support (i.e., from family, peers, and classmates) for PA compared to African American children (Frenn et al, 2005). In a study including over 1,300 Hispanic ninth-and tenthgrade students, from mostly rural schools, Brosnahan et al (2004) examined the relationships among PA, physical education, sadness, and dimensions of suicide.…”
mentioning
confidence: 99%
“…Gender differences in physical activity levels among youth are well documented [1][2][3][4][5]. Less than half the proportion of girls as compared to boys achieve the recommended 60 minutes or more of activity per day in the previous week (11% versus 25%, resp.)…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies have examined these associations longitudinally or with accelerometry measures of PA in adolescents. Further, although a few cross-sectional studies have examined the association between social support and PA in underserved adolescents (i.e., low income, ethnic minorities) (13, 19, 21, 22), an understanding of the importance of social support provided by family and peers for promoting PA over time remains limited in this population.…”
mentioning
confidence: 99%